Circulating Growth Differentiation Factor 15 Levels Are Associated With Risk of Both Intracerebral and Subarachnoid Hemorrhage - Song, Lu; Söderholm, Martin; Svensson, Edith H.; Borné, Yan; Engström, Gunnar (Frontiers in Neurology, 2021)
Growth differentiation factor 15 (GDF-15) has been associated with the risk of developing major bleedings, including but not restricted to intracranial hemorrhages, in patients on oral anticoagulants or dual antiplatelet therapy. We hypothesized that there may be an association of GDF-15 with incidence of hemorrhagic strokes in the general population, which that has not been investigated before. Methods- Two different case-control studies, one for ICH and one for SAH, nested within the population-based Malmö Diet and Cancer cohort, were defined using the incidence density sampling method. GDF-15 was analyzed in frozen blood samples taken at the baseline examination in 1991 to 1996. The associations between GDF-15 and incident ICH (220 cases, 244 controls) and incident SAH (79 cases, 261 controls), respectively, were explored using conditional logistic regression adjusting for risk factors. Results- GDF-15 levels at baseline were higher in both incident ICH cases and SAH cases, compared with their respective control subjects. After adjustment for risk factors, significant relationships with high GDF-15 concentrations were observed both for incident ICH (odds ratio [OR] per 1 log2 unit: 2.27, 95% confidence interval [CI]:1.52-3.41; p=7.1 x 10-5) and incident SAH (OR: 2.16, 95% CI: 1.29-3.59; p=0.0032). Conclusions- High circulating GDF-15 levels were associated with incident ICH and incident SAH, independently of the main risk factors.